Development of Learning Technology in Physical Educa-tion, Sports, and Health at Elementary School : (Study on Third Graders) - Hartini Hartini; Yudi Karisma Sari; Tri Waluyo Basuki; Ciendy Priskilia Jati (LITERACY : International Scientific Journals of Social, Education, Humanities, 2026)
This study aims to develop a contextual and adaptive PJOK (Physical Education, Sports, and Health) learning technology to improve student learning outcomes, particularly in basic motor skills. The research addresses the ineffectiveness of conventional teaching methods in meeting the needs of the digital-native generation. The study used a Research and Development (R&D) approach, based on a modified Borg & Gall model comprising five main stages. The research subjects were third-grade students at SD Negeri Gondangrejo 1, selected through purposive sampling. Data collection methods included classroom observations, structured interviews with PJOK teachers, expert validation questionnaires, and performance tests assessing motor skills such as coordination, balance, agility, speed, and comprehension of instructions. The study revealed a significant improvement in students' posttest scores compared to pretest results in all assessed aspects of motor skills. Expert validation showed that the developed PJOK learning technology had high levels of feasibility, validity, and reliability. This study presents an innovative approach to PJOK instruction by integrating contextual and adaptive technology tailored to the digital-native generation. It offers a practical and effective solution to modernize physical education in elementary schools and enhance students’ motor skill development.